The Policy Implementation of Modern Market Land-Use Control in Municipality of Cirebon - Asterina, Nina; Kurniawan, Teguh (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2014)
The research discusses the policy implementation of modern market land-use control in Cirebon. The modern market development shall cause problems if it does not conform with the regulation of land-use control. This research is qualitative, the data were collected through in-depth interviews, direct observation, and literature study. The results show that the implementation of the policy has not been able to control the modern market. The limiting factor of policy implementation is the business interests of retailers, lack of synergy between traditional and modern market, lack of socialization, monitoring, and limited financial resources. The supporting factors of policy implementation is the awareness of retailers, community support, and mindset of retailers. Recommendations are given to issues such as coordination, policy-instruments reinforcement, policy evaluation, socialization, supervision, and guidance